Forest product trade: 6 lesson for development & conservation (Center for International Forestry Research, 2003)
This video summarizes the six key lessons for interventions based on the findings of CIFOR's NTFP Case Comparison Project that compared 61 cases from Africa, Asia and Latin America. It includes footage from many case study sites, and interviews with NTFP producers and researchers. The video is divided in nine segments; introduction, products and strategies, regional differences, lesson 1: consider context, lesson 3: recognize market opportunities and constraints, lesson 4: local processing adds value, lesson 6: land and resource rights are crucial.